Faktor yang Mempengaruhi PHBS Rumah Tangga di RW 03 Kelurahan Pakunden Kota Blitar - Dimas Pandi Saputro (Journal of Ners and Midwifery, 2016)
The application of a clean and healthy life behavior at home is expected to reduce the risk of disease and improve the quality of health in the family. Clean and healthy life behavior at home is affected by several factors. The factors affecting clean and healthy life behavior at home consists of predisposing, enabling, and reinforcing. The study was conducted to determine the predisposing factors (knowledge, attitudes) in clean and healthy life behavior at home of RW o3 Pakunden Sukorejo Kota Blitar. Method: The method used descriptive exploratory with the sample of 30 families using purposive sampling technique. The instrument used a questionnaire. Result: The result showed that good knowledge category was 93.3% and 56.7% had negative behaviour. Discussion: Factors proven that family behaviour tend to had negative effect in clean and healthy life behavior at home, but the good knowledge category of the family was only at the level of C1 (know). Recommendations from this study that the resident of RW 03 should make the implementation of all indicators of clean and healthy life behavior at home.